Kajian Pemekaran Desa dalam Upaya Pemerataan Pembangunan (Studi Kasus di Desa Persiapan Ngandel Kecamatan Ngrayun Kabupaten Ponorogo) - Sapara, Lusi Ana; Eprilianto, Deby Febriyan (Universitas Negeri Surabaya, 2024)
Regional expansion is the formation of a new region that originates from one parent region, and aims to achieve equitable development that can be enjoyed by all levels of society. Ngandel Preparatory Village proposed expansion to separate itself from its parent village, Cepoko Village. This research aims to analyze the implementation process of village expansion. This research uses a descriptive method with a qualitative approach, focusing on the regulations of Law No. 6/2014 on Villages consisting of age limit, population, socio-culture, infrastructure, village potential, boundaries, transportation access, and operational funds. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through collection, reduction, presentation, verification, and conclusion drawing. The results show that Cepoko Village meets the expansion requirements based on the village age indicator showing that Cepoko Village is 217 years old since its formation in 1817, has a population of 7,484 people/1,871 households, transportation access in Ngandel Preparatory Village is adequate but still requires improvement, socio-cultural conditions including education and health, are adequate, village potential shows that this village has great potential in agriculture, animal husbandry, and small industries, the area boundary indicator has been determined in Ponorogo Regent Regulation No. 36 of 2023, facilities and infrastructure.